How can travelling athletes deal with jet-lag? - Reilly, T. (Kinesiology, 2009)
Sport is a global phenomenon and professional athletes travel across national boundaries for training and for competition. Circadian rhythms are desynchronized when multiple meridians are traversed, leading to the syndrome of jet-lag. Until the body clock has adjusted to the new time zone, many measures of performance are likely to be impaired. Where possible, the travelling athlete should arrive in the new country in enough time for the body clock to adjust to the new time zone. A behavioural approach is preferable to using drugs in coping with jet-lag. Key characteristics of this approach are the timing of exposure to and avoidance of light, avoiding long naps for the transitional period of adjustment and strategic use of exercise. Planning activity on a chronobiological basis can help in ensuring that sports performance is not impaired during the trip or after returning home.